HAMBATAN DAN SOLUSI DALAM KOMUNIKASI POLITIK DI ERA KONTEMPORER - Faridah, Faridah; Suriati, Suriati; Asriadi, Asriadi; Mulkiyan, Mulkiyan; Estuningtyas, Retna Dwi; Yusuf , Muhammad (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
This article aims to examine obstacles and solutions in political communication. The research method is qualitative with the type of library research, with qualitative descriptive analysis. The research results show that communication involving political actors conveying political messages, or relating to power, government and government policy, in the implementation of political communication often encounters various obstacles. The types of political communication barriers include technical barriers, semantic barriers, psychological barriers, physical barriers, organic barriers, status barriers, framework barriers, cultural barriers, and bureaucratic barriers. Paying attention to the many obstacles in political communication and the various solutions offered, then in general The outline of the solution in dealing with political communication obstacles consists of the quality and quantity of political communication, considering media openness, comprehensive and coordinated communication strategy and planning